Wealth inequality: Opportunity for me or for others? - Michael Chaliasos; Thomas Jansson; Yigitcan Karabulut (Goethe University Frankfurt, Institute for Monetary and Financial Stability (IMFS), 2025)
We provide evidence for a new propagation mechanism of wealth inequality and mobility. Using unique administrative data and a quasi-field experiment of exogenous assignment, we find that educated entrants, faced with greater local wealth inequality and salient cases of wealth mobility, take financial, real, and self-employment risks and reach higher positions in the wealth distribution, while the less educated do not. This is driven by poorer communities with more salient cases of wealth mobility, consistent with peer exposure rather than supply-side effects. We find no evidence for other channels, such as obtaining higher-paying more secure jobs, relocating, or reducing debt.
Keywords: G5; E21; E44; D31; D1; 330; Household finance; wealth inequality; education; opportunity; refugees